2003
DOI: 10.1152/ajplung.00215.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase is regulated by ET-1 and MAPKs in peripheral lung microvascular smooth muscle cells

Abstract: -We examined the hypothesis that the potent vasoconstrictor endothelin (ET)-1 regulates both its own production and production of the vasodilator prostaglandins PGE 2 and prostacyclin in sheep peripheral lung vascular smooth muscle cells (PLVSMC). Confluent layers of PLVSMC were exposed to 10 nM ET-1; expression of the prepro (pp)-ET-1, cyclooxygenase (COX)-1, and COX-2 genes was examined by RT-PCR and Western analysis. Intracellular levels of ET-1 were measured by ELISA with and without addition of the protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 41 publications
(52 reference statements)
4
23
0
Order By: Relevance
“…The activation of p38 MAPK was found to be involved in ET-1-stimulated COX-2 expression in cultured feline esophageal smooth muscle cells (25). Chen et al reported that ET-1 treatment results in an increase in the phosphorylation of both p38 and p42/44 MAPKs in peripheral lung microvascular smooth muscle cells (13). Our study demonstrated that the MEK pathway inhibitor, PD98059, as well as the p38 MAPK inhibitor, SB203580, block the ET-1-induced COX-2 expression, indicating that ET-1-mediated effects are likely to be dependent on the MAPK pathway.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The activation of p38 MAPK was found to be involved in ET-1-stimulated COX-2 expression in cultured feline esophageal smooth muscle cells (25). Chen et al reported that ET-1 treatment results in an increase in the phosphorylation of both p38 and p42/44 MAPKs in peripheral lung microvascular smooth muscle cells (13). Our study demonstrated that the MEK pathway inhibitor, PD98059, as well as the p38 MAPK inhibitor, SB203580, block the ET-1-induced COX-2 expression, indicating that ET-1-mediated effects are likely to be dependent on the MAPK pathway.…”
Section: Discussionsupporting
confidence: 62%
“…ET-1 regulates COX-2 expression through p38 and p42/44 MAPK in vascular smooth muscle cells (13) and through p42/44 MAPK in osteoblast-like cells (11). The activation of p38 MAPK was found to be involved in ET-1-stimulated COX-2 expression in cultured feline esophageal smooth muscle cells (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medullary interstitial cells also contain EDNRs but do not produce EDN1 (Dean et al, 1996). Endothelin has been shown to stimulate COX-2 in a variety of mammalian tissues (Hughes et al, 1995;Chen et al, 2003), and EDN1 signaling via endothelial ENDRB results in the production of prostacyclin (Warner et al, 1989;Hirata et al., 1993). Taken together, our findings suggest that during rapid changes in environmental salinity, gill cell survival during this osmotic stress may be accomplished by increased EDN1 production and subsequent stimulation of COX production of prostaglandins.…”
Section: Acute and Chronic Salinity Acclimationsmentioning
confidence: 99%
“…The level of rhoA mRNA was examined by RT-PCR, a simple method that is widely used for semi-quantitative measurement of mRNA levels (e.g., Niiro et al, 1997;Ma et al, 2002;Murray et al, 2002;Chen et al, 2003;Medina et al, 2003;Zhu et al, 2003). Briefly, cDNAs were prepared from the total RNA (0.5 µg) by using a Takara RNA PCR Kit (Ver.…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%